A cluster randomised controlled trial comparing the effectiveness and cost-effectiveness of a school-based cognitive–behavioural therapy programme (FRIENDS) in the reduction of anxiety and improvement in mood in children aged 9/10 years. (2015) - Unknown
No abstract available